PENGARUH PENDAPATAN DAN MASA KERJA TERHADAP KINERJA APARATUR NAGARI DALAM PENGELOLAAN KEUANGAN NAGARI DI KABUPATEN TANAH DATAR - Agnesia Ananta; Syamsir Syamsir (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2019)
The purpose of this study was to determine the effect of income and tenure on the performance of the nagari apparatus in nagari financial management in Tanah Datar District. The background of this study is that there are indications that nagari financial management is still poor in Tanah Datar District. This study uses quantitative research methods. The population of this study is that all nagari apparatus in Tanah Datar District numbered 600 people consisting of walinagari, nagari secretary, nagari treasurer and five nagari affairs heads. The sample in this study consisted of 248 respondents who were determined using the Slovin formula and through the Multi Stage Random Sampling technique. Data collected through questionnaires. The data of this study were analyzed by Anova Test. The results in this study show that there is no significant difference in the performance of nagari financial management based on income and years of service in Tanah Datar District.